Performance Analysis of Unreliable Internet Node - Žvironienė, A.; Navickas, Z.; Rindzevičius, R. (Elektronika ir Elektrotechnika, 2007)
In this article we propose an analysis of the Internet network node, which is using for transmission two unreliable channels with different bit transmission rates. For system with data packet losses the inter arrival time of data packets flow and the transmission times of each channel are exponentially distributed. Heterogeneous transmission channels often occur in the data network when channels are working in parallel. Research is in progress to develop the analytical and simulation models for such data packets transmission system with unreliable channels. Using our proposed analytical model we can easily evaluate asymmetric unreliable data node with packet losses some performance measures. The simulation model was created using the convolution of Moore and Mealy automata. Proposed simulation model is more common than analytical model, because the inter arrival time of data packets and the transmission times of channels can be distributed by various probabilistic distributions. Moreover the analytical system model was applied only for unreliable network node with data packet losses without queuing, whereas the fixed queues are presented in simulation model. Some performance measures results taken by means of analytical and simulation models are presented in figures. lll. 6, bibl. 8 (in English; summaries in English, Russian and Lithuanian).